Socio-economic and geographical inequalities in neonatal mortality rates in Sierra Leone, 2008-2019 - Augustus Osborne; Alpha Umaru Bai-Sesay; Camilla Bangura; Hassan Rogers; Bright Opoku Ahinkorah (BMC, 2024)
Abstract Background Sierra Leone has reduced neonatal mortality rates(NMR) in recent years. Despite this progress, disparities in newborn survival persist across socio-economic and geographic areas. This study examined the inequalities in neonatal mortality rates in Sierra Leone between 2008 and 2019. Methods We utilized data from the Sierra Leone Demographic Health Survey rounds conducted in 2008, 2013, and 2019. We used the World Health Organisation Health Equity Assessment Toolkit to calculate simple measures of inequality (Difference, and Ratio), and complex measures of inequality (Population Attributable Risk, and Population Attributable Fraction). Inequality in neonatal mortality rate was calculated on six stratifiers: maternal age, maternal economic status, maternal level of education, place of residence, sex of the child, and sub-national province. Results Neonatal mortality rate decreased in Sierra Loene from 48.6 deaths per 1,000 live births in 2008 to 29.6 deaths per 1,000 live births in 2019. There was an increase in age-related inequality from a Difference of 0.7 deaths per 1,000 live births in 2008 to 4.3 deaths per 1,000 live births in 2019. Economic inequality decreased from a Difference of 26.8 deaths per 1,000 live births in 2008 to -3.4 deaths per 1,000 live births in 2019. Inequality in education decreased from a Difference of 4.6 deaths per 1,000 live births in 2008 to -4.2 deaths per 1,000 live births in 2019. Inequality increased from a Difference of − 0.5 deaths per 1,000 live births in 2008 to -4.2 deaths per 1,000 live births in 2019 for place of residence. For the child's sex, the inequality increased from a Difference of − 7.9 deaths per 1,000 live births in 2008 to -11.1 deaths per 1,000 live births in 2019. Provincial inequality increased slightly from a Difference of 14.0 deaths per 1,000 live births in 2008 to 14.4 deaths per 1,000 live births in 2019. Conclusion The findings show a decline in the national neonatal mortality rate from 2008 to 2019, indicating improvements in healthcare and maternal support. While economic and educational inequalities have decreased, especially in education, sustaining these gains is essential for equitable healthcare access. Despite this progress, inequalities based on age, residence, child's sex, and province still exist, and have increased between 2008 and 2019. Policymakers should focus on targeted programs for vulnerable age groups and sexes, and develop geographical strategies to ensure uniform improvements in neonatal health.